Regional features of development of tourism on example of Kharkiv’s region - Skril, Iryna (Human Geography Journal, 2016)
The article is devoted to the actual topic – organization of tourism in the Kharkiv’s region and the peculiarities of it’s development. Tourism in Ukraine legally declared priority direction of national culture and economy. In recent decades there have been significant transformations in the development of tourism in Ukraine, which led to the emergence of a number of issues, including spontaneity, uncontrollability, significant territorial inequality of development, imperfection of the legal framework, rapid reorientation to outbound tourism, decreasing rate of domestic tourism etc. Tourism has an important role in regional development. Nowadays, most research is aimed at analysys of economic aspects of development, which is usually associated with external (international) tourism. But not enough attention is paid to social and environmental aspects of domestic tourism, which can be an important tool for spiritual revival and national-patriotic education, formation of ecological thinking and future mentality of the Ukrainian society. Kharkiv’s region has traditionally been kown as a region with a high level of industry, agriculture, education and science. Tourism is not a determining factor in the development of the region, whereas has favorable conditions for that - natural, historical-cultural, economic, social-demographic. The development of tourism in the Kharkiv’s region has certain special aspects: changing ratio of internal and external tourism for the benefit of the external, a small number of foreign tourists, gradually reducing the number of people covered by domestic tourism. Unfortunately, the negative trends in the development of domestic tourism and excursion activity are due to both economic and political problems of last two years. To determine the main directions of development and existing problems in the field of tourism, improving the competitiveness of the regional tourism market, creation of necessary tourist infrastructure in the March 2013 by the decision of the Kharkiv’s regional council was approved the "Concept of tourism development until 2020". The Concept states that the purpose of tourism development in the Kharkiv’s region is the intensification of the industry, increasing of its role in economic and social life of the region through the effective use of tourism potential.